sj-docx-2-sjp-10.1177_14034948221075016 – Supplemental material for Internet-delivered cognitive behavioral therapy (iCBT) for common mental disorders and subsequent sickness absence: a systematic review and meta-analysis ... - Udd-granat, Lina; Lahti, Jouni; Donnelly, Michael; Treanor, Charlene; Pirkola, Sami P.; Lallukka, Tea; Kouvonen, Anne (SAGE Journals, 2022)
Supplemental material, sj-docx-2-sjp-10.1177_14034948221075016 for Internet-delivered cognitive behavioral therapy (iCBT) for common mental disorders and subsequent sickness absence: a systematic review and meta-analysis by Lina Udd-granat, Jouni Lahti, Michael Donnelly, Charlene Treanor, Sami P. Pirkola, Tea Lallukka and Anne Kouvonen in Scandinavian Journal of Public Health ...